Speech Styles Applied by Raymond Chin When Communicating to Faiz Daffa and Hermanto Tanoko - Fransisca Gisela (Institute of Research and Community Outreach - Petra Christian University, 2024)
This study explores Raymond Chin's speech styles when communicating to his younger and older guests on his podcast. In addition, the writer noted the similarities and differences in Raymond Chin's speech styles when communicatingto both his guests. The writer conducted this study using Chaer and Agustina (2004) speech style theory, which was supported by Chaer and Agustina (2010) and Chaer and Agustina (2014). Furthermore, this study was conducted using a qualitative approach. The analysis found that Raymond employed formal, casual, consultative, and exclusion of frozen styles when communicating to both his younger and older guests. Meanwhile, Raymond exclusively employed an intimate style only when communicating to his younger guest. This study also demonstrates that Raymond, either intentionally or not, adapts his style of speech to the ages of his guests. Additionally, Raymond Chin's speech styles do not significantly vary depending on the age of his guests on his podcast.